Time as a Factor of Organization of Aesthetic Reality - Valeryevna Ryazanova, Svetlana (Opción, 2019)
In the article, the problem of the influence of time on the organization of aesthetic reality is considered. The idea that the subjectivity of understan- ding of time is generated by the specifics of human perception is proved. The theoretical and methodological basis of the research is founded on the principles of scientific rationality and dialectics. Besides, in this research, such general scientific methods as comparison, analysis and synthesis were used. The analysis was carried out on the material of several literary and musical texts. As a result, the role and importance of the time component of a work of art in the detection of its semantic content have been disclosed. Based on the conducted research, the following conclusion has been drawn: features of the time organization in a work of art are reflected in its spatial structure and sue to that they become a factor, which influences the solution of an artistic image. Work has a cross-disciplinary character, it is written on a junction of such scientific directions as aesthetics, art criticism, musicolo- gy and literary criticism.